Impact of titanate coated magnetite nanoparticles on the properties of rigid polyurethane foams - Yılmaz, Buse Fem; Kurtlu, Meral Akkoyun; Tuna, Sibel (My University, 2025)
Closed cell polyurethane-based materials represent more than 23% of all polyurethane manufacturing. Unlike to the use of closed cell polyurethane foams in a large variety of applications, these materials exhibit some drawbacks. Their limited mechanical strength and their limited thermal constancy hindering their usage in some areas can be given as examples. In the purpose to overcome and enhance the weaknesses of rigid polyurethane foams and at the same time enlarge the utilization areas of these materials, numerous studies were realized in the literature. The utilization of Fe?O? nanoparticles in various fields, including magnetic resonance, has gained significant attention in recent years. These additives can improve at the same time the thermal and mechanical properties of polyurethane foams. Nevertheless, the development of new methods concerning the surface modification of the nanoparticles is important. The improvement of the interfacial interactions at the polyurethane-filler interface was largely investigated with various agents such as silica, surfactants and precursor metals in the literature. However, the use of a titanate-based coupling agent was not yet researched. In this work, a surface coating of Fe3O4 nanoparticles with a titanate-based coupling agent (Ti-Fe3O4) was realized to produce Fe3O4 filled rigid polyurethane foam nanocomposites at different filler ratios. Microstructural, mechanical, thermal and electrical conductivity properties of all foam nanocomposites were characterized. The FTIR spectra exhibited only the presence of physical interactions. In addition, an increase of the crystallinity ratio with the increase of the filler content was observed. Concerning the electrical and thermal conductivity results, a noticeable improvement was detected from the pure rigid polyurethane foam to the 50 wt.% Ti-Fe3O4 filled nanocomposite. From the mechanical test results, a higher performance was observed for the rigid polyurethane foam nanocomposite produced at 12.5 wt.%.
Keywords: Magnetite; Polymer Composite; Rigid Polyurethane Foam; Titanate Coupling Agent